identité du mois de juin 2015

Posté le : mardi 2 juin 2015 par Vincent Thill
A = 4b(a-3b)(a^2+3ab+6b^2)(a^2+6ab-3b^2)(a^2+2ab+9b^2) B = 2(a+b)(a+3b)(a^2+3b^2)(a^2+15b^2)(a^2+6ab+21b^2) X = (a+b)(a+3b)(a^2+15b^2)(a^2+6ab-3b^2)(a^2+2ab+9b^2) Y = 8b(a-3b)(a^2+3ab+6b^2)(a^2+3b^2)(a^2+6ab+21b^2)

avec    A² + B² = C²    et    X² + Y² = Z²    ainsi que    (A)(B) = (X)(Y)

on a l’équation  :

A^4+B^4+Z^4 = X^4+Y^4+C^4

exemple     a = 2    et    b = 3

(-8050224)^4+(108543710)^4+(91151257)^4=

(9640345)^4+(-90640032)^4+(108841826)^4.

Les commentaires sont fermés